Toward revolutionizing water-energy-food nexus composite index model: from availability, accessibility, and governance - He, Bowen; Zheng, Han; Guan, Qun (Frontiers in Water, 2024)
The water-energy-food nexus has emerged as a critical research interest to support integrated resource planning, management, and security. For this reason, many tools have been developed recently to evaluate the WEF nexus security and monitor progress towards the WEF-related sustainable development goals. Among these, the calculation of the WEF composite index model is critical since it can provide a quantitative approach to demonstrate the WEF nexus security status.However, the current WEF nexus index model framework needs to include the incorporation of governance indicators, neglecting the importance of governance in the WEF nexus framework.Thus, this article develops a new WEF nexus composite index model that incorporates governance indicators in each subpillar is developed. The principal component analysis (PCA) is adopted to reduce the variables' collinearity and the model's dimensionality. A quasi-Monte Carlo based uncertainty and global sensitivity analysis are applied to the index model to assess its effectiveness.Finally, the new WEF index model is applied on the 16 South African Development Community (SADC) countries as a case study. A critical synergy effect within the WEF nexus framework is identified that nations with better WEF governance ability tend to perform better in improving the WEF accessibility capability, suggesting the importance of the governance in the WEF nexus security framework.